PENAMBAHAN ISOLAT PROTEIN KEDELE DAN SUKROSA SEBAGAI ELISITOR TERHADAP SENYAWA ANTIOKSIDAN DAN RACUN PADA KECAMBAH KORO KOMAK (Lablab purpureus L Sweet) - Sukatiningsih Sukatiningsih; Kurniawan Kurniawan; Windrati Windrati (AGROINTEK, 2015)
The germination of “ koro komak ” with elicitation can improve antioxidant substance. Sucrose and ISP on concentration 0, 500, 1000, 1500, 2000 ppm were use as elicitor. The obyective of this research were to know the effect of the kind and the concentration of elicitor to the value of antioxidant substance and the best time of germination produced maximal antioxidant and minimum toxic substance.The result of this research was the kind and the concentration of elicitor influence antioxidant substance and one day is the best time of germination.